HYGIENE SANITASI DAN KELUHAN KESEHATAN KULIT PENGHUNI RUMAH KOST KELURAHAN PADANG BULAN SELAYANG I KECAMATAN MEDAN SELAYANG TAHUN 2013 - moris delmi hawa; wirsal hasan; evi naria (Lingkungan dan Kesehatan Kerja, 2014)
Hygiene, sanitation and health of skin complaints the residents of padang bulan village boarding selayang subdistrict medan selayang I. Complaints of skin health is one thing that is very often experienced by boarder, residents of the boarding school, boarding house residents and also in the form of a typical hives (morning, afternoon, evening or night) and the emergence of full-red swollen bumps on the surface of the skin and itch. Faizal research (2011), in the men's dormitory USU percentage who experience health complaints of skin by 72,4%, the impact of the use of water sourced from the well bore, the behavior of self hygiene boarder who is still lacking, and love swapping clothes with friends This research aims to find out the hygiene sanitation and health of skin complaints the residents of Padang Bulan Village boarding Selayang Subdistrict Medan Selayang I. This research method is descriptive. The population is 536 people and the sample in this study was 100 people. Sampling was done by purposive sampling criteria respondents boarding house residents who have settled >6 months. The results showed that respondents who experienced the health complaints of skin with a sense of the typical hives (morning, afternoon, or night) that as many as 38 people (38.0%), who experience health complaints of skin with red swollen bumps on the surface of the skin and itch that as many as 33 people (33,0%). The conclusions of this research are the complaints of skin health experienced by the occupants of a home boarding The village of Padang Bulan Selayang Subdistrict Medan Selayang I caused because of personal hygiene factors are unfavourable. Boarding house residents are advised to be more attention to personal hygiene and expected to home owners to pay more attention to kost basic sanitation home kost which includes water supply and means of garbage disposal. Keywords: skin health complaints, personal hygiene, basic sanitation